To Develop the Local Wisdom Learning Material Based on Contextual Teaching and Studying for Increasing Social Character - Savira Maharani (RIRAI Publisher, 2024)
This research aims to analyze: (1) the feasibility of Local Wisdom Social Sciences teaching materials based on contextual teaching and learning (CTL) to improve the social character of Class IV MIN 12 students in Medan Tembung District; (2) the practicality of Local Wisdom Social Sciences teaching materials based on contextual teaching and learning (CTL) to improve the social character of Class IV MIN 12 students in Medan Tembung District; (3) analyzing the effectiveness of Local Wisdom Social Sciences teaching materials based on contextual teaching and learning (CTL) to improve the social character of Class IV MIN 12 students in Medan Tembung District. Stages of developing teaching materials with Research & Development (R&D) research using the Thiagarajan 4-D model. This research was carried out at MIN 12 Medan Tembung District, Medan City. The subjects in this research consisted of two classes, namely the experimental class with 24 students and the control class with 23 students. Based on research, it shows that (1) The teaching materials developed are suitable for use to improve students' social character with scores obtained from material experts of 93.8%, language experts of 87.69%, and design experts of 93.10%, with the category